2009
DOI: 10.1093/toxsci/kfp040
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Humoral Immunity by Perfluorooctanoic Acid is Independent of Elevated Serum Corticosterone Concentration in Mice

Abstract: The T-cell-dependent antibody response is suppressed in mice exposed to 3.75, 7.5, 15, and 30 mg PFOA (perfluorooctanoic acid)/kg body weight (bw). Reduced bw accompanied immunosuppression at 15 and 30 mg/kg. We investigated the hypothesis that the observed immunosuppression is secondary to elevated serum corticosterone levels by assessing immune function in adrenalectomized (adx) or sham-operated C57BL/6N female mice exposed to 0, 7.5, or 15 mg PFOA/kg bw in drinking water for 10 days. Bw, primary antibody re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 20 publications
2
40
0
Order By: Relevance
“…In addition, certain inflammatory cytokines produced by keratinocytes, such as IL-18 and IL-33, have the potential to engage the adaptive immune response and can regulate the development of humoral versus cellular immune responses (Moussion et al 2008;Wittmann et al 2009). Since dermal exposure to PFOA was shown to suppress T-cell-dependent IgM and IgG antibodies response and enhance IgE-mediated responses to protein and chemical allergens, evaluation of these cytokines was included in these studies (Anderson et al 2009;Dewitt et al 2008;2009a;2009b;Fairley et al 2007;Yang et al 2001;2002).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, certain inflammatory cytokines produced by keratinocytes, such as IL-18 and IL-33, have the potential to engage the adaptive immune response and can regulate the development of humoral versus cellular immune responses (Moussion et al 2008;Wittmann et al 2009). Since dermal exposure to PFOA was shown to suppress T-cell-dependent IgM and IgG antibodies response and enhance IgE-mediated responses to protein and chemical allergens, evaluation of these cytokines was included in these studies (Anderson et al 2009;Dewitt et al 2008;2009a;2009b;Fairley et al 2007;Yang et al 2001;2002).…”
Section: Discussionmentioning
confidence: 99%
“…Although it was long believed that PFOA was biologically inactive, more recent experiments, using controlled animal studies, showed an association between PFOA exposure and hepatic toxicity, carcinogenicity, reproductive toxicity, hormone disruption, and immunotoxicity (DeWitt et al 2009b). While the majority of animal studies investigated the health effects associated with oral and inhalation routes of PFOA exposure, little is known about the significance of dermal exposure in the human population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, DeWitt et al (2008) demonstrated that suppression of the antigen-specific IgM antibody response occurs at doses that produce no signs of acute toxicity or effects on spleen weight. Furthermore, this group (DeWitt et al (2009a) determined that adrenalectomy did not protect mice from the immunosuppressive effects of PFOA at doses that reduced body weight gain. Although the HPA axis may contribute to immunotoxicity at high doses in intact animals, suppression of humoral immunity at lower doses (e.g., 3.75 and 7.5 mg PFOA/kg PFOA) is independent of elevated corticosterone and therefore represents a true immunotoxic effect (DeWitt et al, 2009a).…”
Section: Evidences Of Immunotoxicity In Rodentsmentioning
confidence: 99%
“…In addition to these hepatic effects, a number of studies have shown that short-term or sub-chronic exposure to relatively high doses of PFOA or PFOS can suppress various aspects of adaptive immunity [28][29][30][31][32][33][34], while at the same time activating the innate branch of the immune system [35].…”
Section: Introductionmentioning
confidence: 99%